Environmental impact assessment practice and participation - Hanna, Kevin S. 1961- (Oxford University Press, 2016)
"Environmental impact assessment (EIA) is among the most influential aspects of environmental regulation and policy today. Environmental Impact Assessment: Practice and Participation examines current debates, recent cases, and ongoing developments in Canadian EIA, accurately reflecting the diversity of issues EIA processes now address. This fully updated third edition has been revised to be even more accessible to student audiences and now provides a more consistent reading level and new chapters on EIA effectiveness, the science of assessment, social impact assessment, Canadian federal EIA, and more. The text offers enhanced and expanded pedagogy, including case studies, questions for critical thought, and a comprehensive glossary, making EIA concepts engaging and accessible."--